Role of Vitamin D Supplementation on Patients of Severe COPD to Reduce Exacerbations (Chest & Heart Journal, 2023)
Background: Vitamin D deficiency is prevalent among patients with chronic obstructive pulmonary disease (COPD) and comes to be more frequent with increased disease severity. Low serum 25-hydroxyvitamin D (25-[OH]D) levels have been associated with lower FEV1, impaired immunologic control and increased airway inflammation which causes frequent exacerbations of COPD patients.Aims: To evaluate the role of vitamin D supplementation on patients of severe COPD to reduce exacerbations.Materials & Methods: This study was prospective observational study conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from December, 2019 to March, 2021. Total 94 severe COPD patients were enrolled in this study, out of which 46 patients were taken in group A that include vitamin D deficiency (